If it's not what You are looking for type in the equation solver your own equation and let us solve it.
w in (-oo:+oo)
w*((3*w+2*w-5+8)/2) = 0
(w*(5*w+3))/2 = 0
( 5*w+3 )
5*w+3 = 0 // - 3
5*w = -3 // : 5
w = -3/5
( w )
w = 0
w in { -3/5, 0 }
| -15=14m+5 | | y/6+9=17 | | 8f-7=65 | | 3x+2x=170 | | 3x=170 | | n/5+7=18 | | 3s-15=75 | | 23x-32=20x-23 | | p/7-3=4 | | 3x^6= | | 9y-30=150 | | t/2-14=36 | | 4u+9=37 | | x/8-1=7 | | -16x-20=13x+7 | | x/12+6=10 | | 4x+0.5y+0.25y=z | | 86-10=x | | m/6+13=19 | | h/6+8=11 | | a/9+7=16 | | w/8+4=8 | | 4x+0.5y+0.25z=1 | | 4x+0.5y+0.25y=1 | | n/9-6=0 | | e/4+14=16 | | u/3+9=18 | | 2(t-3)-3(2t-3)=3-5(3t+1) | | (1/5)(5y+10)-8=(-1/7)(21y-42) | | 8x-3-4x=x+3+x | | (5/6)y-(1/6)=(7/3) | | x-25x/100=7717.95 |